2009
DOI: 10.2140/agt.2009.9.731
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic and finite surgeries on Montesinos knots

Abstract: We give a complete classification of the Dehn surgeries on Montesinos knots which yield manifolds with cyclic or finite fundamental groups.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Our Pretzel knots K s are in the class of a Montesinos knot. In [9], Ichihara and Jong showed that for a hyperbolic Montesinos knot K if K admits a non-trivial cyclic surgery it must be (−2, 3, 7)-pretzel knot and the surgery slope is 18 or 19, and if K admits a non-trivial acyclic finite surgery it must be (−2, 3, 7)-pretzel knot and the slope is 17, or (−2, 3, 9)-pretzel knot and the slope is 22 or 23. In contrast, by this theorem, infinitely many knots in the family of pretzel knot {K s } which appeared in Theorem 1.4 do not admit cyclic or finite surgery.…”
Section: Some Related Topics and Problemsmentioning
confidence: 99%
“…Our Pretzel knots K s are in the class of a Montesinos knot. In [9], Ichihara and Jong showed that for a hyperbolic Montesinos knot K if K admits a non-trivial cyclic surgery it must be (−2, 3, 7)-pretzel knot and the surgery slope is 18 or 19, and if K admits a non-trivial acyclic finite surgery it must be (−2, 3, 7)-pretzel knot and the slope is 17, or (−2, 3, 9)-pretzel knot and the slope is 22 or 23. In contrast, by this theorem, infinitely many knots in the family of pretzel knot {K s } which appeared in Theorem 1.4 do not admit cyclic or finite surgery.…”
Section: Some Related Topics and Problemsmentioning
confidence: 99%
“…, 31}). Finite fillings on this family of Montesinos links was left unresolved in Mattman's extensive study of the problem using character variety methods [30] (Mattman's classification has very recently been completed by Ichihara and Jong applying Heegaard Floer homology techniques [21], and independently treated by Futer, Ishikawa, Kabaya, Mattman and Shimokawa [13]). …”
Section: Introductionmentioning
confidence: 99%
“…It follows from Proposition 4.1 of[18] that the manifold obtained by any rational surgery r ≥ 9 on K is an L-space. So we show that M r,3 cannot bound a negative definite 4-manifold for any r ∈ (0,15]. Towards that end we use Theorem 2.2 and 2.3 of Owens and Strle.We compute the d invariant for the manifold obtained as 15-surgery on P (…”
mentioning
confidence: 78%